Assessing Divisibility in the Armed Career Criminal Act - Koehler, Ted (2012)
When courts analyze whether a defendant's prior conviction qualifies as a violent felony under the Armed Career Criminal Act's residual clause, they use a categorical approach, looking only to the statutory language of the prior offense, rather than the facts disclosed by the record of conviction. But when a defendant is convicted under a divisible statute, which encompasses a broader range of conduct, only some of which would qualify as a predicate offense, courts may employ the modified categorical approach. This approach allows courts to view additional documents to determine whether the jury convicted the defendant of the Armed Career Criminal Act-qualifying part of the statute. This Note identifies a split among the circuit courts regarding when a statute is divisible. Under the formal method, a statute is divisible only when its text specifies qualifying and nonqualifying categories of conduct. By contrast, courts that employ the functional method divide a statute if regardless of the statute's text, it is possible to violate the statute in a way that amounts to a violent felony and in a way that does not amount to a violent felony. This Note contends that the text-based formal method is more consistent with the Supreme Court's Armed Career Criminal Act jurisprudence, the Sixth Amendment, and the rule of lenity. Finally, it argues that the formal method gives Congress the strongest incentive to revise the vague and confusing Armed Career Criminal Act